2016
DOI: 10.1007/s00410-016-1272-6
|View full text |Cite
|
Sign up to set email alerts
|

Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust

Abstract: juvenile character (εHf i +0.5 to +6.5) of Eocene Gangdese arc magmas. Together these two age groups indicate that a component of the xenolith was sourced from Gangdese arc rocks. The 35-20 Ma Miocene ages are derived from zircons with similar Hf-O isotopic composition as the Eocene Gangdese magmatic zircons. They also have similar steep REE curves, suggesting they grew in the absence of garnet. These zircons mark a period of early Miocene remelting of the Eocene Gangdese arc. By contrast, the youngest zircons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…4), calculated by the thermodynamic, phase equilibrium code, Perple_X 36,37 , for relevant temperature regimes 38 . The chosen 39,40 as well as pelite granulite 1 and a global average continental lower crust 41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4), calculated by the thermodynamic, phase equilibrium code, Perple_X 36,37 , for relevant temperature regimes 38 . The chosen 39,40 as well as pelite granulite 1 and a global average continental lower crust 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Calculations were carried out with the Perple_X_6.8.5 phase equilibrium modeling program36 for the internally consistent thermodynamic dataset ds6237 . The composition of rocks is chosen according to xenoliths (felsic granulite and mafic-intermediate granulite) in southern Tibet39,40 as well as a pelite granulite 1 and a global average lower crustal model 41 . a Calculated geotherms for different assumed heat flow values.…”
mentioning
confidence: 99%
“…The Zr, P 2 O 5 , and TiO 2 contents are inversely correlated with SiO 2 (Figure 5b,c), indicating zircon, apatite, and Ti‐bearing mineral had been fractionated from the magma or remained as residues in the source. On the whole, the quartz syenite‐normal granite porphyry magma is likely derived from plagioclase, ilmenite, zircon, apatite bearing source of ancient middle‐upper Lhasa crust, which the mineral assemblages are different from the acid granulite enclaves (Chan et al, 2009; Wang et al, 2016) of ancient Lhasa lower crust (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, increasing studies have revealed that mantle‐derived mafic rocks are sometimes more isotopically enriched relative to the coexisting crustal felsic rocks, contrary to “standard” behavior (e.g., Jiang et al, 2018, and references therein; Shen et al, 2018). Furthermore, magmatic systems with such features commonly occur in regions associated with island arc accretion, such as the Central Asian Orogenic Belt (CAOB) (e.g., Huang et al, 2013; Shen et al, 2009, 2012) and Gangdese Belt (South Tibet) (e.g., Lu et al, 2019; Meng et al, 2019; R. Wang, Richards, Zhou, et al, 2015; Wang et al, 2016; Wang, Collins, et al, 2017; Wang, Weinberg, et al, 2018), but the relationship between the two processes (isotope inversion and island arc accretion) has not been clarified. Recently, Jiang et al (2018) have recognized an “reversed isotope” case in Gan‐Hang Belt (GHB) (South China), where the Neoproterozoic‐aged island arc rocks were locally exposed (Shu et al, 2019; Xia et al, 2018; Yao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%